Implementing Complex Training Method: Its Effects on Endurance, Speed, Power, and Agility of Adolescent Basketball Players - Hadi; Romadhoni, Syahru; Yudhistira, Dewangga (Physical Education Theory and Methodology, 2024)
Objectives. This study aimed to examine the effectiveness of complex training on aerobic endurance, speed, power, and agility in adolescent basketball players. Materials and methods. Field testing experimental research method was used in the study. Purposive sampling was conducted, with participants meeting the following criteria: (1) basketball players training at one club (2) males, (3) having daily training at one club, and (4) being in good health. A total of 16 participants were involved with a body weight of ± 60-80 kg, and a height of 170-190 cm. Observation data collection techniques, review of relevant articles, and tests were used in order to obtain the required material. To ensure the assessment of physical aspects, the following tests and instruments were applied: Jump DF instrument, Multistage fitness test, 20-meter sprint, lane agility test. The Friedman test data analysis technique was performed using the statistical software program SPSS 23. Results. The average score for the first endurance test was 48.53, with the second and third tests demonstrated the results of 50.01 and 52.47, respectively. Similarly, the average speed test score achieved in the first was 3.20, the second was 3.18, and the third — 2.97. The average score for the first agility test was found to be 11.66, the second showed 11.70, and the third — 10.57. The average for the first leg muscle strength test was 66, while the second and third tests were found to be 65 and 69, respectively. The Friedman test variables were used to determine differences in aerobic endurance, speed, power, and agility, the overall significance value was 0.000<0.05. Conclusions. The implementation of a complex training method for 24 sessions provided a significant increase in aerobic endurance, speed, power, and agility of youth basketball players.